2023
DOI: 10.24875/gmm.m22000717
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic cardiomyopathy induces changes in the tryptophan-5-hydroxylase, serotonin transporter and serotonergic receptors expressions

Abstract: Introducción: Los cardiomiocitos poseen la maquinaria bioquímica capaz de sintetizar, utilizar y recapturar serotonina. Objetivo: Determinar si la miocardiopatía hipertrófica (MCH) induce cambios en la expresión de la triptófano-5-hidroxilasa (TPH) 1 y 2, el transportador de serotonina (SERT) y los receptores serotoninérgicos (RS). Métodos: Estudio transversal de cinco bloques de tejido de corazones con MCH y cinco bloques de corazones de control. Se obtuvieron cinco cortes de la pared libre del ventrículo izq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Compared with NCs, HCM patients showed more abnormalities in inflammatory signaling, metabolic pathways and calcium pathways. Previous studies have shown that abnormalities of such pathways in cardiac muscle tissue play an important role in the development of HCM, presenting consistent changes in PBMCs and myocardial tissue in HCM [ 32 ]. Furthermore, DE-miRNAs in PBMCs are more relevant to HCM-related pathogenic pathways than DE-mRNAs, which suggests the importance of circulating miRNA alterations for the pathogenesis of HCM and their potential as diagnostic biomarkers and therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with NCs, HCM patients showed more abnormalities in inflammatory signaling, metabolic pathways and calcium pathways. Previous studies have shown that abnormalities of such pathways in cardiac muscle tissue play an important role in the development of HCM, presenting consistent changes in PBMCs and myocardial tissue in HCM [ 32 ]. Furthermore, DE-miRNAs in PBMCs are more relevant to HCM-related pathogenic pathways than DE-mRNAs, which suggests the importance of circulating miRNA alterations for the pathogenesis of HCM and their potential as diagnostic biomarkers and therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%